Memory, Solitude, and Death in La hoja roja (The Red Leaf), by Miguel Delibes (Castilla. Estudios de Literatura, 2011)
The seventh novel written by Miguel Delibes, La hoja roja (1959) is branded by a recognizable individual style in which is found a double compromise that can’t be easily separated: human –preoccupied with the creation of voracious and intimate characters– and geographical –by utilizing his native Castile, both urban and rural, as the setting for his stories. With the objective of achieving the highest degree of credibility regarding the characters of his novels, Delibes makes use of various narrative techniques, among which it is important to mention one in particular: the fact that his characters have memories. This characteristic, together with the description of with the practices of their everyday lives, contributes to create individuals with a personal past as well as a present where interaction with the rest of the characters results crucial. Paradoxically, within the numerous and varied critical approaches to Delibes’ work, the topic of memory has never been considered as the central element in the investigation, although there are instances in which it is obliquely mentioned. Through these particular stories, that interweave the lives of the principal and secondary characters, Delibes recovers a collective memory as he narrates the present. In the author’s particular vision one can read the direct relationship between solitude and death as a warning on the precarious condition in human relationships in Spain’s society in the fifties, where the main pathology is solitude.